Insights Into Protective Mechanisms of Dandelion Leaf Extract Against Cisplatin-Induced Nephrotoxicity in Rats: Role of Inhibitory Effect on Inflammatory and Apoptotic Pathways - Amira Badr; Dalia Fouad; Hala Attia (SAGE Publishing, 2019)
Cisplatin (CP) nephrotoxicity is associated with the induction of oxidative stress, inflammation, and apoptosis. Several studies demonstrated the antioxidant, anti-inflammatory, and antiapoptotic effects of dandelion leaf extract (DLE); therefore, this research aimed to investigate the protective effects of DLE against CP-induced nephrotoxicity. Thirty-two male Wistar rats were divided into 4 groups: normal control, DLE control received 500 mg/kg daily for 11 days, intoxicated group received vehicle daily for 11 days and a single dose of CP (7 mg/kg, intraperitonealp) on day 5, and DLE + CP group received DLE (500 mg/kg) daily for 11 days plus a single dose of CP (7 mg/kg) on day 5. The dose of DLE is selected based on a dose-effect study using different doses. Dandelion leaf extract pretreatment ameliorated CP-induced nephrotoxicity as evident by histopathological examination, alleviating CP-induced elevation in serum creatinine, blood urea nitrogen, oxidative stress marker (thiobarbituric acid reactive substances), tumor necrosis factor-α (as inflammatory cytokine), and caspase-9 and caspase-3 (as apoptotic markers). In addition, DLE reduced nuclear factor-κB and cytochrome c expression, and DNA fragmentation. It also maintained levels of reduced glutathione, superoxide dismutase, and serum albumin. Thus, the present study shows that DLE is a promising nephroprotective agent for CP-induced nephrotoxicity through antioxidant, anti-inflammatory, and antiapoptotic activities.